English Speaking Anxiety in Language Learning Classroom - Asti Gumartifa; Indawan Syahri (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
English as a foreign language consists of four skills namely, listening, speaking, reading, and writing. These skills have a particular issue that happens differently for each student. For this reason, it's not easy to understand and master the four language skills effectively. Several issues need to overcome first to increase the effectiveness of each ability. Speaking is one of the skills that seem to represent the students' proficiency to speak English. Unfortunately, the majority of Indonesian students, in particular those at the university level, do not provide an appropriate way to speak English proficiently. Students in the 4.0 era are expected to have good communication skills and the ability to socialize with their community. Speaking also requires practice and a deep psychological pleasure that needs to be comfortable. A related study that improves the effectiveness of speaking in language teaching and learning is important. This study is a descriptive study that explains the importance of effective communication in English as a foreign language. This study also provides an opportunity to measure the effectiveness of teaching and learning English speaking skills earlier in the process, which can increase students' confidence and decrease students' anxiety in speaking skills.